Social Change in the Community of Cendana Putih Ii Village, Mappedeceng Subdistrict, North Luwu Regency 2010-2021 - Ridha, Rasyid; ., Nurlaila (KnE Social Sciences, 2024)
The objectives of this study were: 1) To find out the life of the people of Cendana Putih II Village, Mappedeceng District, North Luwu Regency. 2) Factors of social change in Cendana Putih II Village, Mappedeceng District, North Luwu Regency. 3) The impact of social change in Cendana Putih II Village, Mappedeceng District, North Luwu Regency. The research method used in this research is historical research and this research uses seven residents of Cendana Putih II village. Observation, interviews, and documentation were used as data collection techniques. The results of this study concluded he following: 1) Community life before 2010-2021 experienced changes. The beginning of community life in Cendana Putih II village has not yet been formed. 2) The factors driving these changes are internal and external factors, internal factors such as population changes, heterogeneous populations, conflicts or contradictions, and a developing formal education system and external factors due to the influence of other cultures and natural environments. 3) The social change has a positive or negative effect on the social change of the Cendana Putih II village community last year. Keywords: intercultural interaction, multiethnicity, urban environment